Common mental disorder including psychotic experiences: Trailblazing a new recovery pathway within the Improving Access to Psychological Therapies programme in England. Issue 3 (16th May 2017) - Perez, Jesus; Russo, Debra A.; Stochl, Jan; Clarke, James; Martin, Zoe; Jassi, Christina; French, Paul; Fowler, David; Jones, Peter B.
Abstract : Psychotic experiences, depressive and anxiety symptoms may be manifestations of a latent continuum of common mental distress. The Improving Access to Psychological Therapies (IAPT) programme has increased the reach of psychological treatments to people with common mental disorders in England. However, psychotic experiences are neither measured nor considered in therapy. We aimed to confirm the presence of psychotic experiences among IAPT service‐users and determine whether these experiences are associated with higher depression/anxiety levels and poorer recovery. All service‐users that attended the Fenland and Peterborough IAPT teams in Cambridgeshire between November 16, 2015 and January 29, 2016 participated in a service evaluation. In addition to routine mesures, such as the Generalized Anxiety Disorder‐7 questionnaire (GAD‐7) and the Patient Health Questionnaire‐9 (PHQ‐9), we introduced a shortened version of the Community Assessment of Psychic Experiences (CAPE‐P15) to measure psychotic experiences. Classes of individuals were identified with latent class analysis. Associations were reported using Pearson correlation coefficient. One hundred and seventy‐three services‐users were included, mostly females (N = 133; 76.9%). The mean age was 36.6 (SD = 13.3). Around 30% likely belonged to a class with psychotic experiences. CAPE‐P15 frequency was significantly correlated to PHQ‐9 ( r  = 0.44; P  < .001) and GAD‐7 ( r  = 0.32; P  < .001). Similarly, CAPE‐P15 distress and both PHQ‐9 ( r  = 0.43; P  < .001) and GAD‐7 ( r  = 0.38; P  < .001) were highly correlated. These associations were replicated after the initial period of the therapy, indicating poor recovery. Some IAPT service‐users suffer psychotic experiences. Tailoring available evidence‐based psychological therapies for these people in IAPT settings might trailblaze a new care pathway to improve recovery in this group.